2021
DOI: 10.1021/acsabm.0c01544
|View full text |Cite
|
Sign up to set email alerts
|

Anticalcification Potential of POSS-PEG Hybrid Hydrogel as a Scaffold Material for the Development of Synthetic Heart Valve Leaflets

Abstract: Calcification of bioprosthetics is a primary challenge in the field of artificial heart valves and a main reason for biological heart valve prostheses failure. Recent advances in nanomaterial science have promoted the development of polymers with advantageous properties that are likely suitable for artificial heart valves. In this work, we developed a nanocomposite polymeric biomaterial POSS–PEG (polyhedral oligomeric silsesquioxane-polyethylene glycol) hybrid hydrogel, which not only has improved mechanical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…In addition, PPHD had better blood compatibility than PHD, which was consistent with our previous research results. 40 The possible reason is that the addition of silicon- rich POSS nanoparticles with surface roughness and low surface energy can improve the blood compatibility of the material. 50 3.5.…”
Section: Mechanical Properties Of the Scaffoldsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, PPHD had better blood compatibility than PHD, which was consistent with our previous research results. 40 The possible reason is that the addition of silicon- rich POSS nanoparticles with surface roughness and low surface energy can improve the blood compatibility of the material. 50 3.5.…”
Section: Mechanical Properties Of the Scaffoldsmentioning
confidence: 99%
“…The surface hydrophobicity of the scaffold material was greatly improved, which in turn enhanced its anticalcification ability. 40 The underlying mechanism might be that the introduction of POSS nanoparticles increases the hydrophobicity of the surface of the hydrogel, and the binding properties of surface calcium could be adjusted by changing the flow and crystallization of calcium.…”
Section: Mechanical Properties Of the Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…[24,25] It should be noted that many existing studies have demonstrated that valve calcification is one of the most vital problems that lead to the failure of artificial valve scaffolds after in vivo implantation. [26][27][28] Some previous studies found that age had an important influence on valvular calcification. [29] For instance, one study has already demonstrated that younger women (<60 years old) showed less valve calcification than older women.…”
Section: Introductionmentioning
confidence: 99%